2008
DOI: 10.1196/annals.1448.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Circulating Nucleosomes in Cancer

Abstract: Nucleosomes, complexes of DNA and histone proteins, are released during cell death into the blood circulation. Elevated serum and plasma levels have been found in various forms of cancer, but also in autoimmune diseases and acute situations such as stroke, trauma, and during sepsis. Here, the clinical relevance of circulating nucleosomes for diagnosis, staging, prognosis, and therapeutic monitoring of cancer is reviewed. Several studies have shown that levels of nucleosomes are significantly higher in serum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 59 publications
(153 reference statements)
6
113
0
4
Order By: Relevance
“…The origin of serum DNA sequences is controversial. Generally, cell-free DNA in the blood is associated with histones and it is assumed that these circulating nucleosomes originate from apoptotic or necrotic cells in the body, and that the protein-bound DNA is protected from digestion by nucleases (19). Our sequencing approach revealed differences in the relative amounts of different repetitive elements that might reflect a differential nucleosome positioning in the genome of the cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of serum DNA sequences is controversial. Generally, cell-free DNA in the blood is associated with histones and it is assumed that these circulating nucleosomes originate from apoptotic or necrotic cells in the body, and that the protein-bound DNA is protected from digestion by nucleases (19). Our sequencing approach revealed differences in the relative amounts of different repetitive elements that might reflect a differential nucleosome positioning in the genome of the cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of absolute levels of CNAs have been suggested for the diagnosis (13) and prognosis (14) of breast and lung cancer (15). The general diagnostic value of simple quantitative measures of CNA, however, is controversial because nonspecific CNA elevations are seen in patients with benign diseases (16)(17)(18)(19). Cancer-specific DNA perturbations such as microsatellite instability, mutations, sequence length, and promoter methylation patterns detected in serum/plasma have been proposed for the diagnosis and clinical assessment of cancer treatment (20).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of circulating free DNA are detectable in cancer patients including those with SCLC 29 and several studies have supported a role for nDNA in monitoring and predicting clinical outcome. 30 In a recent study of 128 patients with SCLC the utility of nDNA measured immediately before the first three cycles of therapy was compared with a panel of other putative SCLC biomarkers (CYFRA21-1, CEA, NSE, and proGRP). They found that falling levels of all biomarkers, including nDNA, at the start of cycle 2 could be used with reasonable sensitivity and specificity to predict early response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Увеличение количества клеток, вступивших в апоптоз или некроз, приводит к повышению количества нуклеосом в циркуляции [55]. Доказательством этого факта является возрастание концентрации нуклеосом как в плазме, так и в сыворотке крови при различных формах онкологических заболеваний, травмах и сепсисе по сравнению с плазмой/сывороткой крови здоровых доноров [56]. Концентрация нуклеосом в сыворотке не является специфическим признаком [57], концентрация нуклеосом коррелирует со стадией онкологического заболевания и присутствием метастазов только у больных раком желудочно-кишечного тракта [56,58].…”
Section: состав циркулирующих в крови комплексов внеклеточных днкunclassified